The Diversity Intelligent Servant Leader: Developing Leaders to Meet the Needs of a Diverse Workforce. Issue 3 (August 2018) - Sims, Cynthia M.
The Problem: The ability of organizations to realize diversity remains problematic. To meet the needs of the modern workforce, new diversity and leadership approaches are required. The Solution: Diversity intelligence, a promising new human resource development (HRD) tool, leads to enhanced inclusion and equitable treatment in the workplace. Several propositions herein advance that diversity intelligence is an antecedent to the compassionate love servant leadership model. The author describes the potential value diversity intelligent servant leaders provide to society, organizations, leaders, and especially employees with protected class status. This article addresses the implications of the propositions to theory and explores the intersection of servant leadership and diversity and inclusion research streams, practice describes how organizations and HRD professionals can benefit from and implement these arguments, and social impact discusses the benefits society can accrue when all organizational members are engaged, productive and valued. The Stakeholders: This article benefits organizations, leaders, employees, and HRD professionals as well as leadership and diversity and inclusion scholars and practitioners.